Re-conversation or new conversation? Conversation as a necessary condition for creating a „new” school after the pandemic - Bochno, Ewa (Wydawnictwo Naukowe EDUsfera. Ewa Jurczyk-Romanowska, 2021)
In the text, the author uses the recommendations developed by the Centre for Civic Education in the report entitled Szkoła ponownie czy szkoła od nowa? Jak wygląda powrót do stacjonarnej edukacji? The question of what the return to “normal” education looks like, puts an additional condition necessary in modern education, namely the necessity to return to what seems to be the simplest form of communication - conversation. The structure of the text includes (apart from prompting questions and reflection at the end) two main parts. In the first, in relation to the author’s own research, she outlines the picture of school conversations between teachers and students. In the second, she indicates that after the pandemic, the conversation between all subjects of education is one of the key conditions for the school’s culture.
Keywords: conversation; “school after the pandemic”; school